العثمانية الجديدة وإعادة بناءالتقار ب التركي العربي - خجيجة خشعي  عدالة روابحي (جامعة المسيلة, 2024)
The study deals with a detailed presentation of the various aspects related to Turkish-Arab relations and their determinants, variation and homogeneity in them, in light of studying the impact of the dimensions of the Turkish role in the Arab Levant region during the period extending from the year 2002, the date of the arrival of the Islamic-oriented Justice and Development Party to power in Turkey, to the year 2015, and the most important The changes witnessed by Turkey's foreign policy during his rule, as well as the most important factors affecting these relations, especially the determinants Geopolitics, economic, ideological and elite factors, as well as regional and international variables. In the analysis, we used role theory within the framework of international relations, which helps in predicting the role played by the countries that are the subject of the study, based on the analysis of the various data, factors and determinants that constitute the sources of this role, and contributes to the process of linking the research variables and their interactions with each other and knowing the extent of change and development in Its roles during the period of study, as well as the perceptions of the constructivist perspective in international relations, which focuses on ideas and values in shaping the external behaviors of countries determining the pattern of their interactions with the outside world.